Mechanical Load Increases in Bone Formation via a Sclerostin‐Independent Pathway. (November 2014) - Morse, A; McDonald, MM; Kelly, NH; Melville, KM; Schindeler, A; Kramer, I; Kneissel, M; van der Meulen, MCH; Little, DG
ABSTRACT Sclerostin, encoded by the Sost gene, is an important negative regulator of bone formation that has been proposed to have a key role in regulating the response to mechanical loading. To investigate the effect of long‐term Sclerostin deficiency on mechanotransduction in bone, we performed experiments on unloaded or loaded tibiae of 10 week old female Sost−/− and wild type mice. Unloading was induced via 0.5U botulinum toxin (BTX) injections into the right quadriceps and calf muscles, causing muscle paralysis and limb disuse. On a separate group of mice, increased loading was performed on the left tibiae through unilateral cyclic axial compression of equivalent strains (+1200 µe) at 1200 cycles/day, 5 days/week. Another cohort of mice receiving equivalent loads (−9.0 N) also were assessed. Contralateral tibiae served as normal load controls. Loaded/unloaded and normal load tibiae were assessed at day 14 for bone volume (BV) and formation changes. Loss of BV was seen in the unloaded tibiae of wild type mice, but BV was not different between normal load and unloaded Sost−/− tibiae. An increase in BV was seen in the loaded tibiae of wild type and Sost−/− mice over their normal load controls. The increased BV was associated with significantly increased mid‐shaft periosteal mineralizing surface/bone surface (MS/BS), mineral apposition rate (MAR), and bone formation rate/bone surface (BFR/BS), and endosteal MAR and BFR/BS. Notably, loading induced a greater increase in periosteal MAR and BFR/BS in Sost−/− mice than in wild type controls. Thus, long‐term Sclerostin deficiency inhibits the bone loss normally induced with decreased mechanical load, but it can augment the increase in bone formation with increased load. © 2014 American Society for Bone and Mineral Research.